A Community‐Based Walking Program to Promote Physical Activity Among African American Women. Issue 1 (February 2015) - Adams, Titania; Burns, Djuana; Forehand, Jeffery Wade; Spurlock, Amy
Abstract The death rate from cardiovascular disease (CVD) is substantially higher among African American women than for white women. Physical activity has been linked to decreased risk factors and deaths related to CVD. Despite the health benefits of physical activity, reports show most African American women have low levels of physical activity. Home‐ or community‐based walking interventions are effective strategies to promote increased levels of physical activity among African American women. This article describes the implementation of one such program.